2023
DOI: 10.2147/opth.s393662
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Non-Infectious Posterior Uveitis with Dexamethasone Intravitreal Implants in a Real-World Setting

Abstract: The present study aimed to assess the efficacy and safety associated to the treatment of patients with non-infectious posterior uveitis with intravitreal dexamethasone (DEX) implants in a real-world clinical setting. Patients and Methods: This is a retrospective, single center analysis of the data from 29 patients with non-infectious posterior uveitis in whom 38 eyes were treated with dexamethasone intravitreal implants in routine clinical practice between January 2012 and October 2017. The parameters of visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Recent clinical testimonies of the commercially available, FDA-approved intravitreal implant Ozurdec demonstrated its effectiveness in delivering localized dexamethasone and providing visual acuity without causing adverse side effects. However, more research is required to lower the risks of causing increased intraocular pressure and cataract formation [ 198 , 199 , 200 ].…”
Section: Biopolymeric Drugs Delivery Systemsmentioning
confidence: 99%
“…Recent clinical testimonies of the commercially available, FDA-approved intravitreal implant Ozurdec demonstrated its effectiveness in delivering localized dexamethasone and providing visual acuity without causing adverse side effects. However, more research is required to lower the risks of causing increased intraocular pressure and cataract formation [ 198 , 199 , 200 ].…”
Section: Biopolymeric Drugs Delivery Systemsmentioning
confidence: 99%
“…The HURON study ( 2 ) demonstrated that a single dose (0.7 mg) of the IDI was well tolerated and provided significant improvement in visual acuity and intraocular inflammation that persisted for 6 months in patients with non-infectious intermediate or posterior uveitis ( 2 ). Thus, IDI was approved by the United States Food and Drug Administration for the intravitreal treatment of non-infectious uveitis affecting the posterior segment of the eye in 2011 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%